Слепни (Diptera, Tabanidae) долины р. Северского Донца в пределах Луганской области - Шевцова, Н.П.; Сахно, И.И. (Вестник зоологии, 1968)
The data are presented on the results of studying composition of gadflies from the Seversky Donets valley in the Lugansk region. 19 species were found altogether. Seasonal changes are shown in the species composition of the gadfly species which are most frequently met as well as the effect of some environmental factors on the activity of their flight.